2019
DOI: 10.1038/s41598-018-38341-5
|View full text |Cite
|
Sign up to set email alerts
|

eIF5A inhibition influences T cell dynamics in the pancreatic microenvironment of the humanized mouse model of Type 1 Diabetes

Abstract: We have developed a transgenic mouse model of Type 1 Diabetes (T1D) in which human GAD65 is expressed in pancreatic β-cells, and human MHC-II is expressed on antigen presenting cells. Induced GAD65 antigen presentation activates T-cells, which initiates the downstream events leading to diabetes. In our humanized mice, we have shown downregulation of eukaryotic translation initiation factor 5 A (elF5A), expressed only in actively dividing mammalian cells. In-vivo inhibition of elF5A hypusination by deoxyhypusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 78 publications
2
25
0
1
Order By: Relevance
“…It is known that dhps deficiency (the gene encoding DHS) or chronic treatment with DHS inhibitors, as GC7, ameliorate glucose tolerance and glycaemia in various mouse models of diabetes (HFD 30 , 31 , STZ 9 , 32 , humanized mouse model of T1D 33 , db/db 29 ; NOD 34 ). All these exciting studies relied hypusination inhibition effect to beta cell mass protection and decreased pancreas inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that dhps deficiency (the gene encoding DHS) or chronic treatment with DHS inhibitors, as GC7, ameliorate glucose tolerance and glycaemia in various mouse models of diabetes (HFD 30 , 31 , STZ 9 , 32 , humanized mouse model of T1D 33 , db/db 29 ; NOD 34 ). All these exciting studies relied hypusination inhibition effect to beta cell mass protection and decreased pancreas inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…T1DM is considered to be an inflammatory and autoimmune disorder that results from the infiltration of autoreactive T lymphocytes and the consequent generation of proinflammatory cytokines and the appearance of excessive reactive oxygen species (ROS). As a consequence, increased pancreatic β cell death results in hyperglycemia, which is dependent on exogenous insulin administration, concomitantly with evident glucagon secretion imbalance [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of immunosuppression executed by engineered T reg cells towards autologous pathogenic T eff cells can be enhanced by the expression of either the antigen-specific T-cell receptor (TCR) or the chimeric antigen receptor (CAR) on the surface of the T reg cells ( 203 , 204 ). Studies using mouse models of autoimmune diabetes have demonstrated that therapy with antigen-specific T reg cells can improve the targeting of the adoptively transferred cells to specific tissues, and allow the specific recognition of common antigens in autoimmune diseases ( 195 , 205 , 206 ). Therefore, the antigen-specificity of T reg cells can improve their suppressive potency as well as the safety and efficacy of T reg cell-based therapies ( 201 , 207 ).…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%